2015
DOI: 10.1042/bst20150118
|View full text |Cite
|
Sign up to set email alerts
|

Structures and functions of mitochondrial ABC transporters

Abstract: A small number of physiologically important ATP-binding cassette (ABC) transporters are found in mitochondria. Most are half transporters of the B group forming homodimers and their topology suggests they function as exporters. The results of mutant studies point towards involvement in iron cofactor biosynthesis. In particular, ABC subfamily B member 7 (ABCB7) and its homologues in yeast and plants are required for iron-sulfur (Fe-S) cluster biosynthesis outside of the mitochondria, whereas ABCB10 is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 62 publications
1
41
0
Order By: Relevance
“…Western blotting assay (Figure 5c) and real‐time qPCR (Figure 5d) further demonstrated that the expression of ABCB10 in the IR‐780 H cancer cells was higher than it is in IR‐780 L cells. The ABCB10 is a member of the ATP binding cassette energy‐dependent transporters and is demonstrated to responsible for iron import to the mitochondria in previous report 18. Our study identified ABCB10 as an oncogenic relevant gene and was involved in the uptake of IR‐780 by cancer cells.…”
Section: Resultssupporting
confidence: 56%
“…Western blotting assay (Figure 5c) and real‐time qPCR (Figure 5d) further demonstrated that the expression of ABCB10 in the IR‐780 H cancer cells was higher than it is in IR‐780 L cells. The ABCB10 is a member of the ATP binding cassette energy‐dependent transporters and is demonstrated to responsible for iron import to the mitochondria in previous report 18. Our study identified ABCB10 as an oncogenic relevant gene and was involved in the uptake of IR‐780 by cancer cells.…”
Section: Resultssupporting
confidence: 56%
“…Dedicated mitochondrial machineries allow for the import, folding, and assembly of the nuclear-encoded proteins required for proper mitochondrial physiology (72)(73)(74)(75). Mitochondria are also equipped with a family of carriers that facilitate the transport of small soluble molecules like amino acids, nucleotides, and vitamins across the mitochondrial inner membrane, necessary for the interdependent metabolism at both sides of the mitochondrial double membrane (76,77). Mitochondria also play an important role in lipid metabolism (28,29,31,78): it is the site of synthesis of the mitochondrial-specific PLs, CL, and PG, generated from PA, which is imported from the ER (Fig.…”
Section: Making Mitochondrial Membranes: the Contribution Of Er-mitocmentioning
confidence: 99%
“…Two ABC transporters Antimicrobial Agents and Chemotherapy described by our group, ABCI4 and ABCG2, also showed a dual localization and played a role in Sb III resistance (8,9). Several other eukaryotic ABC transporters are found in mitochondria, and most of them belong to the B subfamily of ABC transporters (40). They have often been linked to oxidative stress and iron metabolism in the cytosol and mitochondria (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%